Financial Crises, Investment Slumps, and Slow Recoveries - Cerra, Valerie (IMF Working Papers; Working Paper, 2021)
One of the most puzzling facts in the wake of the Global Financial Crisis (GFC) is that output across advanced and emerging economies recovered at a much slower rate than anticipated by most forecasting agencies. This paper delves into the mechanics behind the observed slow recovery and the associated permanent output losses in the aftermath of the crisis, with a particular focus on the role played by financial frictions and investment dynamics. The paper provides two main contributions. First, we empirically document that lower investment during financial crises is the key factor leading to permanent loss of output and total factor productivity (TFP) in the wake of a crisis. Second, we develop a DSGE model with financial frictions and capital-embodied technological change capable of reproducing the empirical facts. We also evaluate the role of financial policies in stabilizing output and TFP in response to disruptions in financial markets.